DAMPAK IKLIM KERJA, SARANA PRASARANA, MOTIVASI TERHADAP KINERJA PEGAWAI: KEPUASAN KERJA SEBAGAI FAKTOR INTERVENING - Oci Pitriyanti; Anuar Sanusi; Winda Rika Lestari; Anggalia Wibasuri (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to explore the impact of work climate, infrastructure and motivation on employee performance with the role of job satisfaction as an intervening factor at the Sekincau District Office, West Lampung. The research method used is a quantitative and explanatory approach. Data collection techniques include questionnaires, interviews and observations. This research also uses the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The research results show that work climate and infrastructure have a significant effect on employee performance, while motivation has no significant effect. Job satisfaction has a positive and significant effect on employee performance and job satisfaction is proven to mediate the relationship between motivation and employee performance, but does not mediate the relationship between work climate and employee performance, nor does job satisfaction mediate the relationship between infrastructure and employee performance. A work environment and adequate infrastructure directly improve employee performance, while motivation does not have a significant influence. Employee job satisfaction improves performance and acts as a mediator between motivation and performance. Optimizing the work climate, infrastructure and job satisfaction is very important to improve employee performance at the Sekincau District Office.